Kepemimpinan Perempuan Dalam Perspektif Hukum Islam : (Studi Komparatif antara Pemikiran kh. Husein Muhammad dan Asghar Ali Engineer) - Anugrah, Dendy Wahyu; Mahmud, M. Amir (ASASI: Journal of Islamic Family Law, 2023)
Discourse on women to date has been dialectical. Speculative viewpoints that are not in accordance with Islamic rules or law are forcibly used as a reference for supporters of patriarchal culture. Placing women inferior to men is not in accordance with the religious vision of Islam. Different views of scholars regarding the role of women in the public sphere need to be reviewed in order to provide a comprehensive and fair understanding. So, to answer and complement research that continues to answer the dilemmatization of women's leadership, the methods used are library research and comparative studies. The results showed that the thinking of KH. Hussein Muhammad and Asghar Ali Engineer have similarities and differences that are quite clear. Both agreed, supported and explicitly stated that the position of women as leaders is permissible in Islam. However, what is interesting is the difference in methods used by the two Muslim scholars.